2012
DOI: 10.4236/jtts.2012.23023
|View full text |Cite
|
Sign up to set email alerts
|

Likelihood Parameterization of Bicycle Crash Injury Severities

Abstract: This paper evaluates different factors and parameters contributing to likelihood of bicycle crash injury severity levels. Multinomial Logit (MNL) model was used to analyze impact of different roadway features, traffic characteristics and environmental conditions associated with bicycle crash injury severities. The multinomial model was used due to its flexibility in quantifying the effect of the independent variables for each injury severity categories. Model results showed that, severity of bicycle crashes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…All four models identified that intersections and driveways contribute to an increase in crash odds reflecting the findings of previous studies undertaken by Isaksson-Hellman, (2012) for intersections and Chimba et al, (2012) for driveways. Regarding intersections, the findings of this research reflects the findings of previous studies which are of European context (Reynolds et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…All four models identified that intersections and driveways contribute to an increase in crash odds reflecting the findings of previous studies undertaken by Isaksson-Hellman, (2012) for intersections and Chimba et al, (2012) for driveways. Regarding intersections, the findings of this research reflects the findings of previous studies which are of European context (Reynolds et al, 2009).…”
Section: Discussionsupporting
confidence: 77%
“…With regards to infrastructure type, crash risk increases with the presence of driveways (Chimba, Emaasit, & Kutela, 2012), high traffic speeds (Kim, Kim, Ulfarsson, & Porrello, 2007), intersections (Isaksson-Hellman, 2012) and specific road classifications (Li, Zhu, & Sui, 2007) while the presence of bicycle-only infrastructure (e.g., separated cycling facilities, cycle routes and bike lanes) reduces the crash risk compared to mixing with traffic (Reynolds et al, 2009). Of particular interest, in New Zealand and North America, the presence of marked on road cycle lanes has been associated with a crash risk reduction (Parsons & Koorey, 2013;Reynolds et al, 2009) while on a world-wide scale Stewart and McHale (2014) suggest that there is much contradictory evidence surrounding the benefits of cycle lanes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The application of the MNL requires the selection of the base category (Chimba, Emaasit, and Kutela 2012;Liu et al 2015;Salum et al 2019). In this case, the category "no injuries" was used as the base category.…”
Section: Statistical Modeling Methodologymentioning
confidence: 99%